HOME HEALTH NURSES EXPERIENCES WITH FINANCIAL EXPLOITATION OF OLDER ADULTS WITH COGNITIVE IMPAIRMENT - Wilson, J. (Innov Aging, 2017)
Older adult maltreatment often goes unrecognized and unreported in health care. Financial exploitation (FE), a type of older adult maltreatment, is increasing in prevalence as our population ages. Older adults diagnosed with cognitive impairment (CI) who live at home are uniquely at risk for FE due to dependency on caregivers and diminishing financial, cognitive capacities. The purpose of this qualitative descriptive study was to explore how home health registered nurses’ (HHRNs) manage the care and safety of financially exploited older adults with CI. Purposive, sequential, and snowball sampling was used to recruit 20 HHRNs who cared for older adults in the home setting in 44 out of 77 rural and urban Oklahoma counties. Qualitative 45–60 minute telephone interviews were recorded, transcribed, and analysed. Conventional content analysis of the interviews identified five core themes: 1) Investigating FE: Compelled to Keep Looking 2) Familiar Offenders 3) FE Consequences for Older Adults with CI 4) Encountering Facilitators and Barriers and, 5) Frustrations with Systems Gaps. Overall, the HHRNs stressed that systems gaps among health care, law enforcement, and social services blocked communication and collaboration to facilitate the safety of this vulnerable group of exploited older adults with CI. This study showed that HHRNs have expert knowledge of detection, assessment, and reporting of FE of the older adult with CI. HHRNs are an untapped resource to help systems coordinate and improve detection and reporting FE of older adults with CI.